Entomology Faculty Publications as a Source of Information for Collection Development: A Case Study at the University of Arkansas [Abstract only] - Lutishoor Salisbury; Vikramjit Bajwa (Issues in Science and Technology Librarianship)
This study analyzed the entomology faculty publication patterns for the period 1990-1998 by using articles indexed in CAB Abstracts, Biological Abstracts and Agricola. The objectives of this study were to determine if the library was meeting the teaching and research needs of faculty and students in this department. In particular, the study identified in which sources the faculty were publishing, which types of publications the faculty cite, and the age of material cited. The conclusion reached was that our efforts in collection development seem to provide an optimum collection for research in this discipline.